High-thermal-conductivity radiation heat dissipation graphite film and preparation method thereof

Through the high-temperature carbonization and graphitization treatment of modified polyamic acid solution and graphene oxide, combined with dilute sulfuric acid soaking and functionalization treatment, the problems of low thermal conductivity and poor mechanical properties of graphite film are solved, and the preparation of high-thermal conductivity radiant heat dissipation graphite film is realized.

CN119822366AActive Publication Date: 2025-04-15QINGDAO JINGHU NEW MATERIALS CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510135342.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2025-04-15
Estimated Expiration
2045-02-07

AI Technical Summary

Technical Problem

At this stage, the thermal conductivity of graphite film is not high and the mechanical properties are poor, which affects its heat dissipation performance.

Method used

By mixing the modified polyamic acid solution, silver nitrate aqueous solution and graphene oxide, coating it on the substrate after ultrasonic treatment, high-temperature carbonization and graphitization treatment, then soaking in dilute sulfuric acid and functionalized treatment, forming a high-thermal conductivity radiation heat-dissipating graphite film.

Benefits of technology

The thermal conductivity and mechanical properties of the graphite film are significantly improved and its heat dissipation effect is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005263001330000111
    Figure BDA0005263001330000111
Patent Text Reader

Abstract

The invention discloses a high-thermal-conductivity radiation heat dissipation graphite film and a preparation method thereof.The preparation method comprises the steps that a modified polyamide acid solution, a nitric acid solution and graphene oxide serve as raw materials, high-temperature amidation is conducted, a composite film is prepared, high-temperature carbonization graphitization is conducted on the composite film, a composite graphite film is prepared, then the composite graphite film is functionalized, and a functionalized graphite film is prepared; the functional graphite film is soaked in an ethyl acrylate and potassium peroxodisulfate composite liquid, then high-temperature treatment is conducted, the high-heat-conduction radiation heat dissipation graphite film is prepared, in the high-temperature carbonization process, nitrogen can be generated by the N element in the composite film, tiny holes are formed in the surface of the prepared composite graphite film, ethyl acrylate can enter the holes, and the heat dissipation performance of the graphite film is improved. The carbon particles and double bonds on the functionalized graphite film form polyacrylate on holes and the surface, so that the mechanical property of the graphite film is improved, a structure that the carbon particles coat silver can be formed in the high-temperature carbonization process, and the heat conduction effect and the mechanical property of the graphite film are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of graphite film preparation, and in particular to a high thermal conductivity radiation heat dissipation graphite film and a preparation method thereof. Background Art

[0002] With the rapid development of 5G technology, electronic equipment such as smart phones, flat panel displays, and notebooks are becoming lighter, more compact, and more efficient. A large amount of heat will be generated and accumulated during their high-frequency and high-speed operation. If the heat cannot be discharged in time, it will seriously affect the working stability and service life of electronic components. Therefore, there must be a matching thermal solution and specific heat dissipation materials, especially heat dissipation materials with light weight and high thermal conductivity. Traditional metal heat dissipation materials have been difficult to meet the increasingly stringent heat dissipation requirements due to their shortcomings such as high density, high thermal expansion coefficient, and low thermal conductivity. Graphite has excellent properties such as light weight, high thermal conductivity, and easy processing and molding, making it the first choice for heat dissipation materials, but the thermal conductivity between graphite films at this stage is low, and the mechanical properties are not enough and easy to break, which affects normal. Summary of the invention

[0003] The purpose of the present invention is to provide a high thermal conductivity radiation heat dissipation graphite film and a preparation method thereof, which solves the problem that the thermal conductivity of the graphite film at the current stage is not high and the mechanical properties are poor.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A method for preparing a high thermal conductivity radiation heat dissipation graphite film specifically comprises the following steps:

[0006] Step A1: a modified polyamic acid solution, a silver nitrate aqueous solution and graphene oxide are mixed, and ultrasonically treated for 30-40 minutes at a frequency of 20-30 kHz and a temperature of 40-50° C., and then coated on a substrate, and heat-treated at a temperature of 160-170° C. for 3-4 hours, and then heated to 280-300° C., and heat-treated for 2-3 hours, and then removed from the substrate to obtain a composite film;

[0007] Step A2: placing the composite film in a high-temperature carbonization furnace, at a temperature of 600-650°C, under the conditions of an argon and hydrogen volume ratio of 95:5, after heat treatment for 30-40 minutes, heating to 1000°C at a heating rate of 2°C / min, keeping warm for 1-1.5 hours, heating to 1200°C, keeping warm for 1-1.5 hours, to obtain a carbonized film, placing the carbonized film in a high-temperature graphitization furnace, at a heating rate of 5°C, under the conditions of an argon atmosphere, heating to 2300°C, keeping warm for 1-1.5 hours, heating to 2600°C, keeping warm for 1-1.5 hours, to obtain a composite graphite film;

[0008] Step A3: soak the composite graphite film in dilute sulfuric acid, ultrasonically treat it for 2-3 hours at a frequency of 30-40kHz and a temperature of 40-50°C, take it out and dry it, then place it in DMF, add KH550, ultrasonically treat it for 3-5 minutes at a temperature of 60-70°C, add deionized water, ultrasonically treat it for 10-15 minutes, add 4-vinylbenzaldehyde, ultrasonically treat it for 1-1.5 hours to obtain a functionalized graphite film, mix ethyl acrylate and potassium persulfate evenly, soak the functionalized graphite film therein, soak it for 30-40 minutes, take it out until no liquid drops, keep it warm at a temperature of 60-70°C for 2-3 hours to obtain a high thermal conductivity radiation heat dissipation graphite film.

[0009] Furthermore, the amount ratio of the modified polyamic acid solution, the silver nitrate aqueous solution and the graphene oxide described in step A1 is 20 mL:10 mL:3 g, and the mass fraction of the silver nitrate aqueous solution is 1%.

[0010] Further, the mass fraction of the dilute sulfuric acid described in step A3 is 60%, the amount of KH550 added is 1% of the volume of DMF, the amount of deionized water added is 2% of the volume of DMF, the molar ratio of 4-vinylbenzaldehyde and KH550 is 1:1, and the amount of potassium persulfate used is 5‰ of the mass of ethyl acrylate.

[0011] Further, the modified polyamic acid solution is prepared by the following steps:

[0012] Step B1: 4,4'-dibromo-2,2'-dinitrobiphenyl, allyl alcohol, triethylamine and DMF are mixed, and reacted for 3-5 hours at a speed of 200-300 r / min and a temperature of 25-30° C. to obtain intermediate 1; zinc powder, acetic acid, deionized water and DMF are mixed, and stirred and intermediate 1 is added at a speed of 150-200 r / min and a temperature of 80-85° C. to react for 1-1.5 hours, and the pH is adjusted to be alkaline to obtain a modified monomer;

[0013] Step B2: the modified monomer, 4,4'-diaminodiphenyl ether, benzophenone tetracarboxylic dianhydride and DMF are mixed, and the reaction is carried out for 4-6 hours at a speed of 1200-1500 r / min and a temperature of 20-25° C. to obtain a polyamic acid solution, and 2,6-dibromo-4-pyridinemethanol, itaconic acid, p-toluenesulfonic acid and toluene are mixed uniformly, and the reaction is carried out for 3-5 hours at a speed of 200-300 r / min and a temperature of 115-120° C. to obtain an intermediate 2;

[0014] Step B3: The intermediate 2, benzimidazole, copper powder, potassium carbonate, potassium hydroxide and DMF are mixed uniformly, and the reaction is carried out at a speed of 120-150 r / min and a temperature of 155-160° C. for 40-45 hours to obtain a functional monomer, and the polyamic acid solution, acrylonitrile, functional monomer, potassium persulfate and isopropanol are mixed, and the reaction is carried out at a speed of 200-300 r / min and a temperature of 60-70° C. for 3-5 hours to obtain a modified polyamic acid solution.

[0015] Furthermore, the molar ratio of 4,4'-dibromo-2,2'-dinitrobiphenyl, allyl alcohol and triethylamine in step B1 is 1:2:2.1, and the amount ratio of zinc powder, acetic acid, deionized water, DMF and intermediate 1 is 2.5g:2g:20mL:50mL:2g.

[0016] Furthermore, the amount ratio of the modified monomer, 4,4'-diaminodiphenyl ether, benzophenone tetracarboxylic dianhydride and DMF described in step B2 is 1 mol:3 mol:4 mol:1L, the molar ratio of 2,6-dibromo-4-pyridinemethanol and itaconic acid is 1:1, and the amount of p-toluenesulfonic acid is 1% of the mass of itaconic acid.

[0017] Furthermore, the molar ratio of the intermediate 2, benzimidazole, copper powder, potassium carbonate and potassium hydroxide described in step B3 is 5:11:5:5:5, the dosage ratio of the polyamic acid solution, acrylonitrile and functional monomer is 1L:100g:15g, the dosage of potassium persulfate is 0.5% of the total mass of acrylonitrile and functional monomer, and the dosage of isopropanol is 1% of the total mass of acrylonitrile and functional monomer.

[0018] Beneficial effects of the present invention: a high thermal conductivity radiation heat dissipation graphite film disclosed by the present invention is prepared by ultrasonically mixing a modified polyamic acid solution, a nitric acid solution and graphene oxide as raw materials, coating the film on a substrate, removing DMF in the polyamic acid at high temperature, and then subjecting the film to high temperature imidization to obtain a composite film, carbonizing the composite film at high temperature, and further heating the film to graphitization to obtain a composite graphite film, immersing the composite graphite film in dilute sulfuric acid so that the composite graphite film contains active hydroxyl groups, treating the composite graphite film with KH550 so that amino groups are grafted on the surface, and then adding 4-vinylbenzaldehyde so that the aldehyde group on the 4-vinylbenzaldehyde reacts with the amino group on the surface to form an imino group to obtain a functionalized graphite film, immersing the functionalized graphite film in a composite solution of ethyl acrylate and potassium persulfate, and then under high temperature conditions, the double bonds remaining on the surface of the functionalized graphite film will polymerize with the double bonds on the ethyl acrylate to obtain a high thermal conductivity radiation heat dissipation graphite film.

[0019] The modified polyamic acid solution uses 4,4'-dibromo-2,2'-dinitrobiphenyl and allyl alcohol as raw materials for reaction, so that the bromine atom on the 4,4'-dibromo-2,2'-dinitrobiphenyl reacts with the alcohol hydroxyl group on the allyl alcohol to obtain an intermediate 1, and the intermediate 1 is reduced by zinc powder so that the nitro group on the intermediate 1 is converted into an amino group to obtain a modified monomer, and the modified monomer, 4,4'-diaminodiphenyl ether and benzophenone tetracarboxylic dianhydride are reacted to form polyamic acid, and 2,6-dibromo-4-pyridinemethanol and itaconic acid are reacted so that the hydroxyl group on the 2,6-dibromo-4-pyridinemethanol and the carboxyl group on the itaconic acid are esterified to obtain an intermediate 2, and the intermediate 2 is reacted with benzimidazole so that the bromine atom site on the intermediate 2 reacts with the secondary amine on the benzimidazole, and the polyamic acid solution, acrylonitrile and the functional monomer react to form a polyacrylonitrile molecular chain on the side chain of the polyamic acid molecule, and finally the modified polyamic acid solution is obtained.

[0020] During the high-temperature carbonization process, N in the composite film will produce nitrogen, so that the surface of the prepared composite graphite film contains tiny holes. When the functionalized graphite film is immersed in a composite solution of ethyl acrylate and potassium persulfate, ethyl acrylate will enter the holes and form polyacrylate in the holes and on the surface with the double bonds on the functionalized graphite film, thereby increasing the mechanical properties of the graphite film. At the same time, the side walls of the holes can form a stable heat conduction path, thereby ensuring the thermal conductivity of the graphite film. The molecular chain of the modified polyacrylic acid is a comb-like structure, which can form a structure of carbon particles coated with silver during the high-temperature carbonization process, further improving the thermal conductivity and mechanical properties of the graphite film. DETAILED DESCRIPTION

[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Embodiment 1: A method for preparing a high thermal conductivity radiation heat dissipation graphite film, comprising the following steps:

[0023] Step A1: a modified polyamic acid solution, a silver nitrate aqueous solution and graphene oxide are mixed, and ultrasonically treated for 30 minutes at a frequency of 20 kHz and a temperature of 40° C., and then coated on a substrate, and heat-treated at a temperature of 160° C. for 3 hours, and then heated to 280° C., and heat-treated for 2 hours, and then removed from the substrate to obtain a composite film;

[0024] Step A2: placing the composite film in a high-temperature carbonization furnace, at a temperature of 600°C, under the conditions of an argon and hydrogen volume ratio of 95:5, after heat preservation for 30 minutes, heating to 1000°C at a heating rate of 2°C / min, heat preservation for 1 hour, heating to 1200°C, heat preservation for 1 hour, to obtain a carbonized film, placing the carbonized film in a high-temperature graphitization furnace, at a heating rate of 5°C, under the conditions of an argon atmosphere, heating to 2300°C, heat preservation for 1 hour, heating to 2600°C, heat preservation for 1 hour, to obtain a composite graphite film;

[0025] Step A3: The composite graphite film is immersed in dilute sulfuric acid, and ultrasonically treated for 2 hours at a frequency of 30kHz and a temperature of 40°C. The composite graphite film is taken out and dried, and then placed in DMF, KH550 is added, and ultrasonic treatment is performed for 3 minutes at a temperature of 60°C. Deionized water is added and ultrasonic treatment is performed for 10 minutes. 4-vinylbenzaldehyde is added and ultrasonic treatment is performed for 1 hour to obtain a functionalized graphite film. Ethyl acrylate and potassium persulfate are evenly mixed, and the functionalized graphite film is immersed therein for 30 minutes. The composite graphite film is taken out until no liquid drops, and heat-insulated for 2 hours at a temperature of 60°C to obtain a high thermal conductivity radiation heat dissipation graphite film.

[0026] The amount ratio of the modified polyamic acid solution, the silver nitrate aqueous solution and the graphene oxide described in step A1 is 20 mL:10 mL:3 g, and the mass fraction of the silver nitrate aqueous solution is 1%.

[0027] The mass fraction of the dilute sulfuric acid described in step A3 is 60%, the amount of KH550 added is 1% of the volume of DMF, the amount of deionized water added is 2% of the volume of DMF, the molar ratio of 4-vinylbenzaldehyde and KH550 is 1:1, and the amount of potassium persulfate used is 5‰ of the mass of ethyl acrylate.

[0028] The modified polyamic acid solution is prepared by the following steps:

[0029] Step B1: 4,4'-dibromo-2,2'-dinitrobiphenyl, allyl alcohol, triethylamine and DMF were mixed, and reacted at a speed of 200 r / min and a temperature of 25°C for 3 hours to obtain intermediate 1; zinc powder, acetic acid, deionized water and DMF were mixed, and stirred at a speed of 150 r / min and a temperature of 80°C, and intermediate 1 was added to react for 1 hour, and the pH was adjusted to alkaline to obtain a modified monomer;

[0030] Step B2: The modified monomer, 4,4'-diaminodiphenyl ether, benzophenone tetracarboxylic dianhydride and DMF were mixed, and the reaction was carried out for 4 hours at a speed of 1200 r / min and a temperature of 20°C to obtain a polyamic acid solution; 2,6-dibromo-4-pyridinemethanol, itaconic acid, p-toluenesulfonic acid and toluene were mixed uniformly, and the reaction was carried out for 3 hours at a speed of 200 r / min and a temperature of 115°C to obtain an intermediate 2;

[0031] Step B3: Mix intermediate 2, benzimidazole, copper powder, potassium carbonate, potassium hydroxide and DMF evenly, and react at a speed of 120 r / min and a temperature of 155°C for 40 hours to obtain a functional monomer; mix polyamic acid solution, acrylonitrile, functional monomer, potassium persulfate and isopropanol, and react at a speed of 200 r / min and a temperature of 60°C for 3 hours to obtain a modified polyamic acid solution.

[0032] The molar ratio of 4,4'-dibromo-2,2'-dinitrobiphenyl, allyl alcohol and triethylamine in step B1 is 1:2:2.1, and the amount ratio of zinc powder, acetic acid, deionized water, DMF and intermediate 1 is 2.5g:2g:20mL:50mL:2g.

[0033] The amount ratio of the modified monomer, 4,4'-diaminodiphenyl ether, benzophenone tetracarboxylic dianhydride and DMF described in step B2 is 1 mol:3 mol:4 mol:1L, the molar ratio of 2,6-dibromo-4-pyridinemethanol and itaconic acid is 1:1, and the amount of p-toluenesulfonic acid is 1% of the mass of itaconic acid.

[0034] The molar ratio of intermediate 2, benzimidazole, copper powder, potassium carbonate and potassium hydroxide described in step B3 is 5:11:5:5:5, the dosage ratio of polyamic acid solution, acrylonitrile and functional monomer is 1L:100g:15g, the dosage of potassium persulfate is 0.5% of the total mass of acrylonitrile and functional monomer, and the dosage of isopropanol is 1% of the total mass of acrylonitrile and functional monomer.

[0035] Embodiment 2: A method for preparing a high thermal conductivity radiation heat dissipation graphite film, comprising the following steps:

[0036] Step A1: a modified polyamic acid solution, a silver nitrate aqueous solution and graphene oxide are mixed, ultrasonically treated for 35 minutes at a frequency of 25 kHz and a temperature of 45° C., and then coated on a substrate, and heat-treated at a temperature of 165° C. for 3.5 hours, then heated to 290° C., and heat-treated for 2.5 hours, and then removed from the substrate to obtain a composite film;

[0037] Step A2: placing the composite film in a high-temperature carbonization furnace, at a temperature of 630°C, under the conditions of an argon and hydrogen volume ratio of 95:5, after heat preservation for 35 minutes, heating to 1000°C at a heating rate of 2°C / min, heat preservation for 1.3 hours, heating to 1200°C, heat preservation for 1.3 hours, to obtain a carbonized film, placing the carbonized film in a high-temperature graphitization furnace, at a heating rate of 5°C, under the conditions of an argon atmosphere, heating to 2300°C, heat preservation for 1.3 hours, heating to 2600°C, heat preservation for 1.3 hours, to obtain a composite graphite film;

[0038] Step A3: The composite graphite film is immersed in dilute sulfuric acid, and ultrasonically treated for 2.5 hours at a frequency of 35kHz and a temperature of 45°C. Then, it is taken out and dried, and then placed in DMF, KH550 is added, and ultrasonic treatment is performed for 4 minutes at a temperature of 65°C. Deionized water is added and ultrasonic treatment is performed for 13 minutes. 4-vinylbenzaldehyde is added and ultrasonic treatment is performed for 1.3 hours to obtain a functionalized graphite film. Ethyl acrylate and potassium persulfate are evenly mixed, and the functionalized graphite film is immersed therein for 35 minutes. The film is taken out until no liquid drops, and heat preservation treatment is performed at a temperature of 65°C for 2 hours to obtain a high thermal conductivity radiation heat dissipation graphite film.

[0039] The amount ratio of the modified polyamic acid solution, the silver nitrate aqueous solution and the graphene oxide described in step A1 is 20 mL:10 mL:3 g, and the mass fraction of the silver nitrate aqueous solution is 1%.

[0040] The mass fraction of the dilute sulfuric acid described in step A3 is 60%, the amount of KH550 added is 1% of the volume of DMF, the amount of deionized water added is 2% of the volume of DMF, the molar ratio of 4-vinylbenzaldehyde and KH550 is 1:1, and the amount of potassium persulfate used is 5‰ of the mass of ethyl acrylate.

[0041] The modified polyamic acid solution is prepared by the following steps:

[0042] Step B1: 4,4'-dibromo-2,2'-dinitrobiphenyl, allyl alcohol, triethylamine and DMF were mixed, and the mixture was reacted for 4 hours at a speed of 200 r / min and a temperature of 30°C to obtain intermediate 1. Zinc powder, acetic acid, deionized water and DMF were mixed, and the mixture was stirred at a speed of 150 r / min and a temperature of 85°C, and intermediate 1 was added to the mixture, and the mixture was reacted for 1.3 hours. The pH was adjusted to be alkaline to obtain a modified monomer.

[0043] Step B2: The modified monomer, 4,4'-diaminodiphenyl ether, benzophenone tetracarboxylic dianhydride and DMF were mixed, and the reaction was carried out at a speed of 1200 r / min and a temperature of 25°C for 5 hours to obtain a polyamic acid solution; 2,6-dibromo-4-pyridinemethanol, itaconic acid, p-toluenesulfonic acid and toluene were mixed uniformly, and the reaction was carried out at a speed of 200 r / min and a temperature of 120°C for 4 hours to obtain an intermediate 2;

[0044] Step B3: Mix intermediate 2, benzimidazole, copper powder, potassium carbonate, potassium hydroxide and DMF evenly, and react at a speed of 120 r / min and a temperature of 160°C for 40 hours to obtain a functional monomer; mix polyamic acid solution, acrylonitrile, functional monomer, potassium persulfate and isopropanol, and react at a speed of 200 r / min and a temperature of 65°C for 4 hours to obtain a modified polyamic acid solution.

[0045] The molar ratio of 4,4'-dibromo-2,2'-dinitrobiphenyl, allyl alcohol and triethylamine in step B1 is 1:2:2.1, and the amount ratio of zinc powder, acetic acid, deionized water, DMF and intermediate 1 is 2.5g:2g:20mL:50mL:2g.

[0046] The amount ratio of the modified monomer, 4,4'-diaminodiphenyl ether, benzophenone tetracarboxylic dianhydride and DMF described in step B2 is 1 mol:3 mol:4 mol:1L, the molar ratio of 2,6-dibromo-4-pyridinemethanol and itaconic acid is 1:1, and the amount of p-toluenesulfonic acid is 1% of the mass of itaconic acid.

[0047] The molar ratio of intermediate 2, benzimidazole, copper powder, potassium carbonate and potassium hydroxide described in step B3 is 5:11:5:5:5, the dosage ratio of polyamic acid solution, acrylonitrile and functional monomer is 1L:100g:15g, the dosage of potassium persulfate is 0.5% of the total mass of acrylonitrile and functional monomer, and the dosage of isopropanol is 1% of the total mass of acrylonitrile and functional monomer.

[0048] Embodiment 3: A method for preparing a high thermal conductivity radiation heat dissipation graphite film, comprising the following steps:

[0049] Step A1: a modified polyamic acid solution, a silver nitrate aqueous solution and graphene oxide are mixed, and ultrasonically treated for 40 minutes at a frequency of 30 kHz and a temperature of 50° C., and then coated on a substrate, and heat-treated at a temperature of 170° C. for 4 hours, and then heated to 300° C., and heat-treated for 3 hours, and then removed from the substrate to obtain a composite film;

[0050] Step A2: placing the composite film in a high-temperature carbonization furnace, at a temperature of 650°C, under the conditions of an argon and hydrogen volume ratio of 95:5, after heat preservation for 40 minutes, heating to 1000°C at a heating rate of 2°C / min, heat preservation for 1.5 hours, heating to 1200°C, heat preservation for 1.5 hours, to obtain a carbonized film, placing the carbonized film in a high-temperature graphitization furnace, at a heating rate of 5°C, under the conditions of an argon atmosphere, heating to 2300°C, heat preservation for 1.5 hours, heating to 2600°C, heat preservation for 1.5 hours, to obtain a composite graphite film;

[0051] Step A3: The composite graphite film is immersed in dilute sulfuric acid, and ultrasonically treated for 3 hours at a frequency of 40kHz and a temperature of 50°C. The composite graphite film is taken out and dried, and then placed in DMF, KH550 is added, and ultrasonically treated for 5 minutes at a temperature of 70°C. Deionized water is added and ultrasonically treated for 15 minutes. 4-vinylbenzaldehyde is added and ultrasonically treated for 1.5 hours to obtain a functionalized graphite film. Ethyl acrylate and potassium persulfate are mixed evenly, and the functionalized graphite film is immersed therein for 40 minutes. The composite graphite film is taken out until no liquid drops, and the composite graphite film is heat-insulated at a temperature of 70°C for 3 hours to obtain a high thermal conductivity radiation heat dissipation graphite film.

[0052] The amount ratio of the modified polyamic acid solution, the silver nitrate aqueous solution and the graphene oxide described in step A1 is 20 mL:10 mL:3 g, and the mass fraction of the silver nitrate aqueous solution is 1%.

[0053] The mass fraction of the dilute sulfuric acid described in step A3 is 60%, the amount of KH550 added is 1% of the volume of DMF, the amount of deionized water added is 2% of the volume of DMF, the molar ratio of 4-vinylbenzaldehyde and KH550 is 1:1, and the amount of potassium persulfate used is 5‰ of the mass of ethyl acrylate.

[0054] The modified polyamic acid solution is prepared by the following steps:

[0055] Step B1: 4,4'-dibromo-2,2'-dinitrobiphenyl, allyl alcohol, triethylamine and DMF were mixed, and reacted at a speed of 300 r / min and a temperature of 30° C. for 5 h to obtain intermediate 1; zinc powder, acetic acid, deionized water and DMF were mixed, and stirred at a speed of 200 r / min and a temperature of 85° C., and intermediate 1 was added to react for 1.5 h, and the pH was adjusted to alkaline to obtain a modified monomer;

[0056] Step B2: The modified monomer, 4,4'-diaminodiphenyl ether, benzophenone tetracarboxylic dianhydride and DMF were mixed, and the reaction was carried out for 6 hours at a speed of 1500 r / min and a temperature of 25°C to obtain a polyamic acid solution; 2,6-dibromo-4-pyridinemethanol, itaconic acid, p-toluenesulfonic acid and toluene were mixed uniformly, and the reaction was carried out for 5 hours at a speed of 300 r / min and a temperature of 120°C to obtain an intermediate 2;

[0057] Step B3: Mix intermediate 2, benzimidazole, copper powder, potassium carbonate, potassium hydroxide and DMF evenly, and react at a speed of 150 r / min and a temperature of 160°C for 45 hours to obtain a functional monomer; mix polyamic acid solution, acrylonitrile, functional monomer, potassium persulfate and isopropanol, and react at a speed of 300 r / min and a temperature of 70°C for 5 hours to obtain a modified polyamic acid solution.

[0058] The molar ratio of 4,4'-dibromo-2,2'-dinitrobiphenyl, allyl alcohol and triethylamine in step B1 is 1:2:2.1, and the amount ratio of zinc powder, acetic acid, deionized water, DMF and intermediate 1 is 2.5g:2g:20mL:50mL:2g.

[0059] The amount ratio of the modified monomer, 4,4'-diaminodiphenyl ether, benzophenone tetracarboxylic dianhydride and DMF described in step B2 is 1 mol:3 mol:4 mol:1L, the molar ratio of 2,6-dibromo-4-pyridinemethanol and itaconic acid is 1:1, and the amount of p-toluenesulfonic acid is 1% of the mass of itaconic acid.

[0060] The molar ratio of intermediate 2, benzimidazole, copper powder, potassium carbonate and potassium hydroxide described in step B3 is 5:11:5:5:5, the dosage ratio of polyamic acid solution, acrylonitrile and functional monomer is 1L:100g:15g, the dosage of potassium persulfate is 0.5% of the total mass of acrylonitrile and functional monomer, and the dosage of isopropanol is 1% of the total mass of acrylonitrile and functional monomer.

[0061] Comparative Example 1: Compared with Example 1, no silver nitrate aqueous solution was added to this comparative example, and the remaining steps were the same.

[0062] Comparative Example 2: Compared with Example 1, this comparative example uses a functionalized graphite film instead of a high thermal conductivity radiation heat dissipation graphite film, and the other steps are the same.

[0063] Comparative Example 3: Compared with Example 1, this comparative example uses a polyamic acid solution instead of a modified polyamic acid solution, and the remaining steps are the same.

[0064] The graphite films prepared in Examples 1-3 and Comparative Examples 1-3 were tested for in-plane thermal conductivity and interlayer thermal conductivity according to GB / T22588-2008, and Type 5 specimens were made according to GB / T1040.3-2006. The tensile rate was 50 mm / min, and the test results are shown in Table 1 below.

[0065] Table 1

[0066]

[0067] It can be seen from the above table that the present application has good thermal conductivity and high mechanical strength.

[0068] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a high thermal conductivity radiation heat dissipation graphite film, characterized in that: The specific steps include: Step A1: after ultrasonic treatment for 3 times, a modified polyamic acid solution, a silver nitrate aqueous solution and graphene oxide are mixed and coated on a substrate, and after high-temperature heat preservation treatment, the substrate is removed from the substrate to obtain a composite film; Step A2: placing the composite film in a high-temperature carbonization furnace, carbonizing it at high temperature to obtain a carbonized film, placing the carbonized film in a high-temperature graphitization furnace, graphitizing it at high temperature to obtain a composite graphite film; Step A3: After soaking the composite graphite film in dilute sulfuric acid and ultrasonically treating it, take it out and dry it, then put it in DMF, add KH550, ultrasonically treat it, add deionized water, ultrasonically treat it, add 4-vinylbenzaldehyde, and ultrasonically treat it to obtain a functionalized graphite film, mix ethyl acrylate and potassium persulfate evenly, soak the functionalized graphite film therein, soak it, take it out until no liquid drops, and keep it warm to obtain a high thermal conductivity radiation heat dissipation graphite film.

2. The method for preparing a high thermal conductivity radiation heat dissipation graphite film according to claim 1, characterized in that: The amount ratio of the modified polyamic acid solution, the silver nitrate aqueous solution and the graphene oxide described in step A1 is 20 mL:10 mL:3 g, and the mass fraction of the silver nitrate aqueous solution is 1%.

3. The method for preparing a high thermal conductivity radiation heat dissipation graphite film according to claim 1, characterized in that: The mass fraction of the dilute sulfuric acid described in step A3 is 60%, the amount of KH550 added is 1% of the volume of DMF, the amount of deionized water added is 2% of the volume of DMF, and the molar ratio of 4-vinylbenzaldehyde to KH550 is 1:

1.

4. The method for preparing a high thermal conductivity radiation heat dissipation graphite film according to claim 1, characterized in that: The modified polyamic acid solution is prepared by the following steps: Step B1: 4,4'-dibromo-2,2'-dinitrobiphenyl, allyl alcohol, triethylamine and DMF are mixed and reacted to obtain intermediate 1, zinc powder, acetic acid, deionized water and DMF are mixed and stirred and added to intermediate 1 to react, and the pH is adjusted to alkaline to obtain a modified monomer; Step B2: mixing and reacting the modified monomer, 4,4'-diaminodiphenyl ether, benzophenone tetracarboxylic dianhydride and DMF to obtain a polyamic acid solution, and mixing and reacting 2,6-dibromo-4-pyridinemethanol, itaconic acid, p-toluenesulfonic acid and toluene to obtain an intermediate 2; Step B3: The intermediate 2, benzimidazole, copper powder, potassium carbonate, potassium hydroxide and DMF are mixed and reacted to obtain a functional monomer, and the polyamic acid solution, acrylonitrile, the functional monomer, potassium persulfate and isopropanol are mixed and reacted to obtain a modified polyamic acid solution.

5. The method for preparing a high thermal conductivity radiation heat dissipation graphite film according to claim 4, characterized in that: The molar ratio of 4,4'-dibromo-2,2'-dinitrobiphenyl, allyl alcohol and triethylamine in step B1 is 1:2:2.1, and the amount ratio of zinc powder, acetic acid, deionized water, DMF and intermediate 1 is 2.5g:2g:20mL:50mL:2g.

6. The method for preparing a high thermal conductivity radiation heat dissipation graphite film according to claim 4, characterized in that: The modified monomer, 4,4'-diaminodiphenyl ether, benzophenone tetracarboxylic dianhydride and DMF described in step B2 are used in a ratio of 1 mol:3 mol:4 mol:1 L, and the molar ratio of 2,6-dibromo-4-pyridinemethanol and itaconic acid is 1:

1.

7. The method for preparing a high thermal conductivity radiation heat dissipation graphite film according to claim 4, characterized in that: The molar ratio of the intermediate 2, benzimidazole, copper powder, potassium carbonate and potassium hydroxide described in step B3 is 5:11:5:5:5, and the amount ratio of the polyamic acid solution, acrylonitrile and functional monomer is 1L:100g:15g.

8. A high thermal conductivity radiation heat dissipation graphite film, characterized in that: Prepared according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • High-thermal conductivity graphite alkenyl polymer heat conducting film and preparation method thereof

    CN104592950A

  • Method for preparing high thermal conductivity graphite film by using graphene-doped polyamic acid resin

    CN106853966A

  • Preparation method of multi-component hybridized anisotropic heat-diffusion film

    CN109575456A

  • Preparation method of polyimide / graphene composite carbon film

    CN110240150A

  • Preparation method of heat-conducting gasket with high normal heat conductivity and high elasticity

    CN112679765A